Bringing earth observation to classrooms: the importance of out-of-school learning places and e-learning - Dannwolf, Lisa; Matusch, Tobias; Keller, Johannes; Redlich, Ronja; Siegmund, Alexander (Remote sensing, 2020)
Viewing the Earth from above has fascinated people at least since the Apollo mission in the 1960s. Today, satellite images have made their way into the news and media, but the potential of using satellite images in the classroom has not yet been exhausted. Teachers often lack the technical knowledge of Earth observation (EO) or the technical requirements in schools. The Geo:spektiv e-learning platform used provides the opportunity to integrate EO into curricula as well as current environmental- and space-relevant topics. This study analyses the driving forces that determine the motivation of students and which factors contribute to the success of an e-learning platform. The basis for this study is a Geo:spektiv module about the endangered rainforest, established at an out-of-school learning place and designed for students in secondary education. A survey of 281 students on their motivation and learning behavior showed, that in addition to the topic and level of difficulty tailored to the students’ needs, the design of the modules, simple navigation, and the use of multimedia content are vital. Despite the small sampling size and restricted geographical location of sample selection, the results of this study can contribute to better integration of digital geo-media in school lessons.